Comparative Efficacy of Intralesional Tranexamic Acid and Platelets Rich Plasma (Prp) In The Treatment of Melasma - Aslam, Sana; Muzaffar, Bushra; Siddiqui, Muhammad Adeel; Hussain, Majid; Sajjad, Danyal; Farid , Huma (Pakistan Armed Forces Medical Journal, 2026)
Objective: To study the efficacy of intralesional tranexamic acid compared to platelets rich plasma (PRP) in treatment of melasma. Study Design: Randomized Controlled Trial (ClinicalTrials.gov Identifier: NCT05884151). Place and Duration of Study: Department of Dermatology, CMH (Combined Military Hospital) Abbottabad, from Nov 2022 to April 2023. Methodology: Sample size of 60 patients, aged 20 to 40 years, was calculated by using OpenEpi online calculator. Informed consent was taken and patients were randomly allocated to two groups: Group A, where 30 patients were injected with intradermal tranexamic acid (4 mg/ml) and Group B, where 30 patients were treated with PRP (1 ml) intra-dermally, every fourth week, for up to 12 weeks between both groups. The modified Melasma Area and Severity Index (mMASI) was used to evaluate all patients. The final evaluation was performed on the 24th week of follow-up. For data analysis Statistical Package for the Social Sciences (SPSS) version 27.00 was used. To determine statistical significance, a paired t-samples test was used where p-value was <0.05. Results: Of the 60 patients randomly assigned to two groups, Group A had mean age of 30.23+5.24 years while Group B had mean age of 29.50+5.83 years. The majority of patients were females 47(78.30%). Overall, 31(51.70%) patients had malar pattern of melasma (p-value=0.030) while 46(76.70%) patients had mixed melasma (p-value=0.015). While comparing pre-treatment efficacy, mMASI score in Group A was 1.. Conclusions: Tranexamic acid was found to be highly effective and safer than PRP with patient compliance being better due to no pain.